A CASE REPORT: HYPERTENSION IN PREGNANCY - Sagung Desy Kristiyani (Universitas Udayana, 2014)
Hypertension in pregnancy is 15 percent of the comorbid of pregnancy and one of the threehighest causes of maternal mortality and morbidity in childbirth. This can be either ChronicHypertension, Gestational Hypertension,and developed further into Preeclampsia orEclampsia. In Indonesia, the mortality and morbidity of hypertension in pregnancy is alsostill quite high. This is caused not only by the etiology that is stillunclear, but also bychildbirth care that is still handled by non-medical officers and referral system which hasnot been perfect. This case report discusses about Severe Preeclampsia with ImpendingEclampsiaon a 28 years old pregnant woman, supporting urinalysis examination showedprotein and ketones in the urine, blood chemistry examination also obtained an increase ofthe liver enzyme and lactate dehydrogenase . In these patients is done handling atermination of pregnancy by Sectio Caesarea method.